‘General History’, ‘Content-Oriented Philosophy’ of History, and the Theory of Evolution - Horský, Jan (Dějiny – teorie – kritika, 2019)
Horský in his discussion paper analyses the relation between ‘general history’ and ‘content-oriented philosophy’ of history. This helps him approach the subject of the role of philosophy of history in historical and scientific research. He uses the term ‘content-oriented philosophy of history’ in a broad sense, that is, including its classical conceptions (August Comte, G.W.F. Hegel, Karl Marx), its innovated forms (for instance Ernst Cassirer’s philosophy of culture), as well as its variants which approach the subject from the perspective of historical sociology (Max Weber, Alfred Weber, Norbert Elias). Aside from that, the author investigates the relation between general history and other sciences or research directions which deal with development or processual changes (especially evolutionary biology) and their investigations to some extent overlap with some forms of content-oriented philosophy (‘history’, ‘life’, etc.). And last but not least, Horský investigates whether some claims (describing a state of affairs, developmental tendencies, and the like) made within the framework of ‘general history’ or against its background could also aspire to being true in a scientific sense of the term. It is concluded that there is indeed some overlap between content-oriented philosophy of history and general history. General history can be a field where some concepts originating in the content-oriented philosophy of history can be (quasi)empirically checked and some of its parts can be translated into theories in a narrower sense of the term. Nevertheless, where content-oriented philosophy of history or general (biological or culturological) theory of evolution is used as the background of general history, it must be taken into account, duly considered, and thereby also checked. The same holds if general history functions as a necessary background of any formulation of research-worthy subject of historical sciences: in such case, its presence or influence must likewise be duly reflected. Back to contents Download article